A graceful embrace : theological reflections on adopting children - Swinton, John, 1957- (Theology in Practice, 2017)
This book significantly deepens the contemporary discussion of the theology and practice of adopting children. Though adoption appears prominently in Scripture, contemporary adoption practice has thus far proceeded without serious theological engagement. This book seeks to fill this gap by offering a theological and ethical perspective on adoption that not only clarifies and complicates contemporary understandings of adoption, but also throws fresh light on family, community, vocation, and even what it means to be human. Both interdisciplinary and international, the volume is brings together theologians and ethicists from Europe, the UK, Canada and the United States. A rich set of reflections from both practical and theoretical perspectives offers a unique and uniquely insightful vision of Christian adoption. Contributors are: Dale P. Andrews, Jana Marguerite Bennett, Marco Derks, R. Ruard Ganzevoort, Bill McAlpine, Kirsten Sonkyo Oh, Sarah Shea, Paul Shrier, Henning Theißen, Hans. G. Ulrich, Karin Ulrich-Eschemann, Heather Walton, Brent Waters, Nick Watson.